Heavy Metal Pollution Status and Potential Ecological Risk Assessment in Farmland Surface Soil Along River in Jiaozuo Area - Li, Yujie (International Journal of Natural Resources and Environmental Studies, 2024)
A total of 41 surface soil samples were collected from the farmlands along Guangliji River and Jianggou River in Jiaozuo area, and 7 heavy metals such As Cr, Cu, Zn, AS, Cd, Pb and Ni were determined by ICP-MS (Varian-820).The soil accumulation index method, single factor pollution index method, Nemerow comprehensive pollution index method and potential ecological risk index method were used to evaluate the pollution status and potential ecological risk of heavy metals in the study area. The results showed that compared with the risk screening value (pH>7.5) given in the "Soil Quality Standard for Soil Pollution Risk Control of Agricultural Land" (GB15618-2018), Cd in farmland soil along the two rivers exceeded the screening value by 5.7 times and 1.5 times, respectively, and was the main local pollutant. The Nemero comprehensive pollution index of the farmland along Guangliji River and Jianggou River was 9.71 and 1.88, respectively, which were in the level of heavy pollution and light pollution. The comprehensive potential ecological risk index of farmland along the two rivers is 417.65 and 85.79, with strong ecological risk and slight ecological risk respectively. The comprehensive evaluation shows that there is a certain degree of heavy metal pollution in the farmland soil along the river in Jiaozuo area, especially Cd pollution, and the ecological risk in some areas has exceeded the acceptable level, which should arouse the attention of the local government and relevant departments.